O efeito da concentração regional das indústrias sobre o desempenho das firmas: uma abordagem multinível - Ferreira, Fernando Coelho Martins (2009)
This work had as objective to assess the relation between industrial concentrations and the financial performance of firms located in these places. Literature review sustained the formulation of the hypotheses of this work, which were based on the assumption that location in industrial concentrations provides firms superior return on assets, operational return on assets, asset turnover and organizational slack, when compared to non concentrated firms. Manufacturing industry of the state of São Paulo was the sector chosen for this analysis. For the mapping of industrial concentrations, data on the number of jobs and enterprises from RAIS databank was used, referring to 1996-2005 period. The identification of industrial concentrations allowed SERASA – a company focused on the analysis and information for credit decisions and support to businesses – to elaborate a database of companies located in the state of São Paulo, based on the provision of a list of all industrial sectors characterized by the presence of industrial concentrations. Initially with 8.637 records, the base was reduced to 4.280 records, corresponding to 509 firms belonging to 23 different industries. After data selection, the variable that identifies the areas of the state of São Paulo with industrial concentrations was added to SERASA databank, allowing, therefore, the fulfillment of the analyses of this work. By using the statistical technique of multilevel modeling, it was possible to conclude that there is not enough evidence to claim that location in industrial concentration provides firms superior return on assets, operational return on assets, asset turnover or organizational slack, when compared to non concentrated firms. However, decomposition of variance of these indicators allowed to conclude that “city’ and the way “city” and an “industry” interact play a major role in determining the variability of these indicators. This result suggests that location does matter to the way firms will perform. Analyses still allowed the estimation of the effect of each interaction between industry and city on the proposed indicators. Besides the great variability of these effects, it was not detected a significant difference between the effects of interactions with and without industrial concentrations. Therefore, other factors specific to these interactions, rather than industrial concentrations, would be able to explain why some interactions have very positive effects on their firms, while other have very low or negative effects. Limitations inherent to this work keep results from being generalized. However, one believes that its contributions are able to show new possibilities of research on the field of industrial concentration, so to understand the real importance of this phenomenon for the competitiveness of companies.